Integrins α4β1 and αVβ3 are Reduced in Endothelial Progenitor Cells from Diabetic Dyslipidemic Mice and May Represent New Targets for Therapy in Aortic Valve Disease. (25th August 2020) - Filippi, Alexandru; Constantin, Alina; Alexandru, Nicoleta; Voicu, Geanina; Constantinescu, Cristina Ana; Rebleanu, Daniela; Fenyo, Madalina; Simionescu, Dan; Simionescu, Agneta; Manduteanu, Ileana; Georgescu, Adriana
Diabetes reduces the number and induces dysfunction in circulating endothelial progenitor cells (EPCs) by mechanisms that are still uncovered. This study aims to evaluate the number, viability, phenotype, and function of EPCs in dyslipidemic mice with early diabetes mellitus and EPC infiltration in the aortic valve in order to identify possible therapeutic targets in diabetes-associated cardiovascular disease. A streptozotocin-induced diabetic apolipoprotein E knock-out( ApoE −/− ) mouse model was used to identify the early and progressive changes, at 4 or 7 days on atherogenic diet after the last streptozotocin or citrate buffer injection. Blood and aortic valves from diabetic or nondiabetic ApoE −/− animals were collected. EPCs were identified as CD34 and vascular endothelial growth factor receptor 2 positive monocytes, and the expression levels of α4 β1, αV β3, αV β5, β1, αL β2, α5 integrins, and C-X-C chemokine receptor type 4 chemokine receptor on EPC surface were assessed by flow cytometry. The number of CD34 positive cells in the aortic valve, previously found to be recruited progenitor cells, was measured by fluorescence microscopy. Our results show that aortic valves from mice fed 7 days with atherogenic diet presented a significantly higher number of CD34 positive cells compared with mice fed only 4 days with the same diet, and diabetes reversed this finding. We also show a reduction of circulatory EPC numbers in diabetic mice caused by cell senescence and lower mobilization. Dyslipidemia induced EPC death through apoptosis regardless of the presence of diabetes, as shown by the higher percent of propidium iodide positive cells and higher cleaved caspase-3 levels. EPCs from diabetic mice expressed α4β1 and αV β3 integrins at a lower level, while the rest of the integrins tested were unaffected by diabetes or diet. In conclusion, reduced EPC number and expression of α4β1 and αVβ3 integrins on EPCs at 4 and 7 days after diabetes induction in atherosclerosis-prone mice have resulted in lower recruitment of EPCs in the aortic valve.